2020
DOI: 10.1016/j.msea.2020.140008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TiC content on microstructure and mechanical properties of nickel-based hastelloy X nanocomposites manufactured by selective laser melting

Abstract: The nickel-based Hastelloy X (HX) superalloy is widely applied in the aerospace industry because of its exceptional oxidation resistance and various beneficial properties at high temperatures. HX-based nanocomposites manufactured by additive-manufacturing processes based on powder-bed fusion, such as selective laser melting (SLM), are expected to further enhance the material's mechanical and thermophysical performance. This paper systematically studies the effects of TiC nanoparticle content on the microstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…For modification of the resulting microstructure of the AM-built component, nanoparticulate grain refiners can be employed as well. Han et al (2019); Han et al (2020) prepared surfacefunctionalized Hastelloy X powder with 1 wt% of TiC nanoparticles in a high speed mixer and investigated the effect of TiC on AM processibility, resulting microstructure and mechanical part properties. They confirmed that TiC functionalization induced formation of increased low angle grain boundaries leading to crack-free parts with tensile strength and elongation at break increased by 10 % and 19%, respectively.…”
Section: Nickel Alloy Feedstock Powdersmentioning
confidence: 99%
“…For modification of the resulting microstructure of the AM-built component, nanoparticulate grain refiners can be employed as well. Han et al (2019); Han et al (2020) prepared surfacefunctionalized Hastelloy X powder with 1 wt% of TiC nanoparticles in a high speed mixer and investigated the effect of TiC on AM processibility, resulting microstructure and mechanical part properties. They confirmed that TiC functionalization induced formation of increased low angle grain boundaries leading to crack-free parts with tensile strength and elongation at break increased by 10 % and 19%, respectively.…”
Section: Nickel Alloy Feedstock Powdersmentioning
confidence: 99%
“…Cutting force issues are frequently encountered in the aerospace manufacturing industry due to nickel-based superalloys that tend to be more difficult to machine compared to other traditional materials. Hastelloy X or Inconel HX is one of the most widely used nickel-based superalloys for aerospace components, such as structure [1] and gas turbine engines for the combustion zone components [2][3][4][5]. Taking into consideration that aerospace components have to accomplish certain temperature and oxidation resistance [1][2][3][4][5], it has helped to drive demand for this superalloy.…”
Section: Introductionmentioning
confidence: 99%
“…The above studies mainly focused on the effects of reinforcement on the microstructure and mechanical performance of MMCs through experimental investigations. These studies also revealed that the migration of added reinforced particles was strongly connected to the components' mechanical performance [13]. Conducting real-time observations to obtain a comprehensive understanding of the reinforcements' movement is challenging, however, due to the complex physical phenomena that occur during experimentation.…”
Section: Introductionmentioning
confidence: 99%
“…the indicator: laser energy density (๐œŽ = ๐‘ƒ ๐‘‰ * ๐‘™ * โ„Ž), where ๐‘ƒ and ๐‘‰ represent the laser power and scanning speed; ๐‘™ and โ„Ž denote the powder layer thickness and hatch spacing, respectively[35]. The optimum laser energy density to manufacture nearly fully dense HX-1 wt.% TiC composite specimens was determined to 83.3 J/mm 3 (๐‘ƒ = 200 W, โ„Ž = 100 ฮผm, ๐‘™ = 40 ฮผm and ๐‘ฃ = 600 mm/s).…”
mentioning
confidence: 99%